(X^25)^-6/(x-^3)^48 simplify
![X256x348 simplify class=](https://us-static.z-dn.net/files/d44/dfe4e5229095d49008df2399f9e58145.png)
Answer:
[tex]x^{-6}[/tex]
Step-by-step explanation:
using the rules of exponents
• [tex](a^m)^{n}[/tex] = [tex]a^{mn}[/tex]
• [tex]\frac{a^{m} }{a^{n} }[/tex] = [tex]a^{m-n}[/tex]
simplifying numerator/ denominator
[tex]\frac{x^{25(-6)} }{x^{-3(48)} }[/tex]
= [tex]\frac{x^{-150} }{x^{-144} }[/tex]
= [tex]x^{-150-(-144)}[/tex]
= [tex]x^{-150+144}[/tex] = [tex]x^{-6}[/tex]